Mengukur Efektivitas Corporate Social Responsibility (CSR) dalam Menciptakan Nilai Perusahaan pada Industri Tekstil di Indonesia - Khasanah, Midhatul; Hadi, Zufli Amrullah; Firmansyah, Rizky; Restuningdiah, Nurika (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Corporate Social Responsibility (CSR) has become a hot topic in the business world today. However, there is still debate regarding the influence of CSR on company value. Textile companies are a sector that has a big impact on the environment and surrounding communities. Therefore, social responsibility is a very important issue for textile companies. The aim of this research is to determine the influence of CSR on company value in textile companies listed on the Indonesia Stock Exchange for the 2018-2022 period. This research method uses descriptive and quantitative research methods. The population in this study were 14 textile companies. Researchers used the purposive sampling method for sampling. Data analysis and hypothesis testing using SPSS version 26. An investor is expected to be able to consider everything when making an investment, including how the company manages funds, especially investor funds, to generate maximum profits. As well as how the company expresses its social responsibility both to society and the environment regarding the impact of its operational activities. So that the natural environment and everything in it can still be maintained and used sustainably.